Diagnostic Efficacy and Prognostic Recurrence Prediction Effect of Regulatory T Cells plus TGF-β1 in Pediatric Patients with Allergic Rhinitis and Concurrent Adenoid Hypertrophy - Lan, Ning; Chen, Weibin; Guo, Lingyun; Huang, Yongping (Journal of Medical Biochemistry, 2025)
Objective: The co-occurrence of adenoid hypertrophy (AH) and allergic rhinitis (AR) is known to be linked to immune microenvironment disruptions. This research was designed to assess how regulatory T cells (Treg) and transforming growth factor-β1 (TGF-β1) perform in diagnosing AH in pediatric AR cases and in predicting the likelihood of post-treatment recurrence. Methods: From February 2023 to June 2024, 127 children diagnosed with AR alone (AR group) and 134 children with AR-AH comorbidity (AR+AH group) were recruited. All participants were followed prospectively for a 12-month period. Peripheral blood Treg counts were measured using flow cytometry, while serum TGF-β1 concentrations were determined via enzyme-linked immunosorbent assay (ELISA). Diagnostic effectiveness was evaluated using receiver operating characteristic (ROC) curves. A Logistic regression model was developed to forecast recurrence risk, with model parameters refined by incorporating relevant clinical features. Results: AR+AH cases exhibited statistically lower Treg counts and TGF-β1 levels than their AR counterparts (P<0.001). When Treg and TGF-β1 were combined for prediction, the area under the curve (AUC) reached 0.858, along with 91.04% sensitivity and 71.65% specificity—performance that outperformed either marker used individually (P<0.001). Following treatment, the increases in Treg and TGF-β1 levels were less pronounced in the AR+AH group than in the AR group (P<0.001). The follow-up data indicated 42 cases of recurrence, whose post-treatment Treg and TGF-β1 levels remained lower relative to those who did not experience a recurrence (P<0.05). A composite predictive model, integrating age, adenoid-to-nasopharynx (A/N) ratio, Treg, and TGF-β1, yielded an AUC of 0.869, with sensitivity and specificity being 95.24% and 68.48%, respectively. Conclusion: A synergistic effect is observed when Tregs and TGF-β1 are measured together, enhancing the diagnostic accuracy for AR-AH co-occurrence. Furthermore, their combination with clinical characteristics optimizes stratification of recurrence risk.